2018
DOI: 10.1097/lgt.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Human Papillomavirus Detection in Urine Samples From a Referral Population With Cervical Biopsy-Proven High-Grade Lesions

Abstract: Although these results demonstrated slightly higher detection rates for HR-HPV and clinical sensitivity in cervical samples than in urine, when compared with histological diagnoses, urine sampling is a viable alternative to access women who do not participate in routine screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 11 publications
2
18
2
Order By: Relevance
“…The HPV DNA test's sensitivity for CIN2/3 detection using urine samples in the current study is higher than reported by previous studies that used Cobas HPV test [21,22], but lower than reported from studies that used the Trovagene platform [24,26]. The specificity obtained was overall higher than reported from studies that used Trovagene and Cobas HPV tests [22,24,26,27]. The higher sensitivity obtained in our study in comparison with other studies that used Cobas HPV test might be explained by the use of an EDTA preservative solution for our specimens.…”
Section: Plos Onecontrasting
confidence: 81%
See 1 more Smart Citation
“…The HPV DNA test's sensitivity for CIN2/3 detection using urine samples in the current study is higher than reported by previous studies that used Cobas HPV test [21,22], but lower than reported from studies that used the Trovagene platform [24,26]. The specificity obtained was overall higher than reported from studies that used Trovagene and Cobas HPV tests [22,24,26,27]. The higher sensitivity obtained in our study in comparison with other studies that used Cobas HPV test might be explained by the use of an EDTA preservative solution for our specimens.…”
Section: Plos Onecontrasting
confidence: 81%
“…Detection of HPV DNA in paired urine and cervical specimens has given inconsistent results with the detection of cervical intraepithelial neoplasia (CIN) 2 or greater (2+), yielding sensitivities ranging from 63 to 95% and specificities of 23 to 89% [18][19][20][21][22][23][24][25]. Recent data derived from use of the Trovagene test has resulted in relatively high sensitivity for high-grade precancerous lesions in higher risk colposcopy referral patients [26,27]. Urine-based HPV DNA testing remains an attractive alternative to increase screening coverage, mainly among women subgroups that cervical HPV detection is difficult [28].…”
Section: Introductionmentioning
confidence: 99%
“…Sahasrabuddhe et al found that urine used for Trovagene HPV assay showed 92.3% sensitivity for cervical cancer precursors in a pilot study in referral population. Another similar study reported that in 350 patients diagnosed previously with CIN2+, urine was detected by Trovagene HPV assay, and had 83.4% sensitivity and 50.8% specificity against CIN2+ .…”
Section: Discussionmentioning
confidence: 57%
“…Another similar study reported that in 350 patients diagnosed previously with CIN2+, urine was detected by Trovagene HPV assay, and had 83.4% sensitivity and 50.8% specificity against CIN2+. 26 And the sensitivity and specificity for urine detected by cobas4800 HPV test and Linear Array were 80.0% and 78.0% for CIN2+, respectively, in women with previous HPV-positive. 28 Compared with above studies, in our research, urine showed similar sensitivity for CIN2+ at baseline, and the specificity was higher, which may be attributed to heterogeneities among studies, such as HPV test utilized.…”
Section: Clinical Performance For Paired Samplesmentioning
confidence: 88%
See 1 more Smart Citation